2015
DOI: 10.1159/000371344
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction: Effects on Neural Precursor Cell Proliferation and Angiogenesis in the Foetal Subventricular Zone

Abstract: Exposure to adverse prenatal factors can result in abnormal brain development, contributing to the aetiology of several neurological disorders. Intrauterine insults could occur during neurogenesis and gliogenesis, disrupting these events. Here we investigate the effects of chronic placental insufficiency (CPI) on cell proliferation and the microenvironment in the subventricular zone (SVZ). At 30 days of gestation (DG; term ∼67 DG), CPI was induced in pregnant guinea pigs via unilateral uterine artery ligation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…The remaining primary antibodies discussed below were used as tissue markers or have extensive published data supporting their validity. Tissue marker staining appeared in the expected pattern of cellular morphology and those Western blotted demonstrated the band sizes of expected MW as found in previous publications: α‐Notch‐1 (Kostyszyn, Cowburn, Seiger, Kj, & Sundstrom, ), α‐Sox‐2 (Wang et al, ), α‐nestin (Frederiksen & McKay, ; Yoshimatsu et al, ), α‐vimentin (Lavado & Oliver, ; Middeldorp et al, ), α‐GFAP (Lee, Han, Lee, Park, & Kim, ; Middeldorp et al, ), α‐ and β‐III tubulin (Lee et al, ; Menezes & Luskin, ), α‐O4 (Sommer & Schachner, ; Windrem et al, ), α‐Bax (Wnuk, Rzemieniec, Litwa, Lason, & Kajta, ; Xiao & Zhang, ), α‐Bcl‐2 (Li, Chen, & Zhou, ; Xiao & Zhang, ), α‐doublecortin (Corbo et al, ; Mizuguchi, Qin, Yamada, Ikeda, & Takashima, ), α‐Ki67 (Tolcos et al, ). Further details of primary antibodies are given in Table .…”
Section: Methodssupporting
confidence: 78%
See 1 more Smart Citation
“…The remaining primary antibodies discussed below were used as tissue markers or have extensive published data supporting their validity. Tissue marker staining appeared in the expected pattern of cellular morphology and those Western blotted demonstrated the band sizes of expected MW as found in previous publications: α‐Notch‐1 (Kostyszyn, Cowburn, Seiger, Kj, & Sundstrom, ), α‐Sox‐2 (Wang et al, ), α‐nestin (Frederiksen & McKay, ; Yoshimatsu et al, ), α‐vimentin (Lavado & Oliver, ; Middeldorp et al, ), α‐GFAP (Lee, Han, Lee, Park, & Kim, ; Middeldorp et al, ), α‐ and β‐III tubulin (Lee et al, ; Menezes & Luskin, ), α‐O4 (Sommer & Schachner, ; Windrem et al, ), α‐Bax (Wnuk, Rzemieniec, Litwa, Lason, & Kajta, ; Xiao & Zhang, ), α‐Bcl‐2 (Li, Chen, & Zhou, ; Xiao & Zhang, ), α‐doublecortin (Corbo et al, ; Mizuguchi, Qin, Yamada, Ikeda, & Takashima, ), α‐Ki67 (Tolcos et al, ). Further details of primary antibodies are given in Table .…”
Section: Methodssupporting
confidence: 78%
“…The remaining primary antibodies discussed below were used as tissue markers or have extensive published data supporting their va- (Li, Chen, & Zhou, 2013;Xiao & Zhang, 2008), α-doublecortin (Corbo et al, 2002;Mizuguchi, Qin, Yamada, Ikeda, & Takashima, 1999), α-Ki67 (Tolcos et al, 2015). Further details of primary antibodies are given in Table 1.…”
Section: Antibody Characterizationmentioning
confidence: 99%
“…Previous studies indicate the reduction of neural progenitor cells after hypoxic damage and the presence of immature neuronal cells or apoptotic cells (38,43). Tolcos et al (27) found that although cell proliferation increased, the weight of the brain was decreased. These results suggest the variability of the intrauterine micro-environment.…”
Section: Discussionmentioning
confidence: 99%
“…The Image-Pro Plus 7.0 image analysis software program (Media Cybernetics, Inc., Rockville, MD, USA) was used by three investigators to measure the densities of the NeuN-, BDNF-, PI3K-, Akt-, and phospho-Akt (pAkt)-IR cells (cells/mm 2 ). The density of positive cells was counted within five randomly chosen defined field similarly as in a previous study (15).…”
Section: Methodsmentioning
confidence: 99%